Study On The Quality Of Agricultural Extension Services Related To The Level Of Farmer Satisfaction In Tulehu Village, Sub-District Salahutu Central Maluku Regency Maluku Province - Ricard Porotjo; Melvis E.Tahitu; Risat A. Far (Cita konsultindo, 2024)
The implementation of agricultural extension activities is a series of sustainable processes in accordance with the needs of the main actors (farmers), for which agricultural extension materials and methods are part of the quality of agricultural extension activities. The quality of agricultural extension can be determined by comparing the satisfaction of farmers with the services received with the services expected by farmers. The purpose of this study is to determine the quality of agricultural extension services, farmer satisfaction and farmer capacity in the development of farming in Salahutu District, Central Maluku Regency, Maluku Province and to find out the relationship between the quality of extension services and the level of farmer satisfaction. This research was carried out in Tulehu Village from October 2023 to November 2023. The type of research used is census research. The total population in this study is 30 farmers in Tulehu village and the sample in this study is the total or the entire population. The data collected includes primary data and secondary data with the data analysis technique used being qualitative descriptive data analysis. The results show that the quality of extension services and farmer satisfaction are in the medium category and the level of correlation can be said that farmer satisfaction has almost met the expectations of the service.